2021
DOI: 10.1080/1331677x.2021.1875863
|View full text |Cite
|
Sign up to set email alerts
|

The importance of green practices for hotel guests: does gender matter?

Abstract: Due to growing consumer awareness of environmental problems, more and more hotels have been developing green practices in response to the environmental concerns of their guests and improve their image. This study aimed to test a model for analyzing the incidence of green practices as drivers for generating positive hotel image and guest trust and satisfaction, evaluating the moderating role of guest gender in these relationships. Based on a personal survey of 302 guests at 3 and 4-star hotels in Bogot a, evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
65
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(75 citation statements)
references
References 82 publications
8
65
0
2
Order By: Relevance
“…All results presented in the previous section confirm that there is a direct relationship between the green brand image, trust, satisfaction and loyalty, as argued by Martinez [12] Assaker et al [41], Bashir et al [5], and Assaker, G. [3,34]. Other works, such as Wang et al [2] and Mercade et al [13], only used green word of mouth communication instead of green loyalty.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…All results presented in the previous section confirm that there is a direct relationship between the green brand image, trust, satisfaction and loyalty, as argued by Martinez [12] Assaker et al [41], Bashir et al [5], and Assaker, G. [3,34]. Other works, such as Wang et al [2] and Mercade et al [13], only used green word of mouth communication instead of green loyalty.…”
Section: Discussionsupporting
confidence: 71%
“…In this context, several academics have considered that image plays a very relevant role in consumer satisfaction [33,34]. Thus, Chen's [16] research work confirmed the relationship between the green brand image and green satisfaction in the electronic products and services sector in Taiwan.…”
Section: Satisfaction As a Consequence Of The Green Imagementioning
confidence: 88%
See 2 more Smart Citations
“…Consequently, this work aims to examine consumer perceptions in relation to innovative and sustainable practices implemented by retailers, and examine their effect on consumer satisfaction. In addition, considering the discrepancies that exist in the marketing literature about the existence, or not, of differences in the perceptions of these actions between men and women (Contreras et al, 2016;Meuter et al, 2005;Moise et al, 2021;Torres and Arroyo-Cañada, 2016;Weijters et al, 2007), it is relevant to make progress in this regard in the context of retail trade. Therefore, this study adopts the approach of previous research arguing that the current business model in retailing must be built from a dual perspective to ensure success in the market: retailing must be innovative and sustainable.…”
Section: Introductionmentioning
confidence: 99%